2021
DOI: 10.18311/jbc/2021/23837
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on biology of <i>Chelonus blackburni</i> (Cameron) (<i>Hymenoptera:Braconidae</i>) on <i>Phthorimaea operculella</i> (Zeller) and <i>Corcyra cephalonica</i> (Stainton) under laboratory conditions

Abstract: <em>Chelonus blackburni</em> (Cameron) that parasitizes eggs of potato tuber moth is widely distributed and occurs commonly in potato fields throughout the country. Studies on its biology and ovipositional performance were carried out on both hosts i.e. <em>Phthorimaea operculella</em> and <em>Corcyra cephalonica</em> in laboratory conditions. Average number of eggs laid per female was found to be 210.9 ± 16.62 on <em>P. operculella</em> and 118.4 ± 7.49 on <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Although there were no reports to date indicating either of the insect species identified in stored sesame seeds in Ethiopia, our current findings were consistent with earlier research that suggested that C. cephalonica was noted as a significant sesame storage pest in India (Babu et al 2020;Dilipsundar et al 2019). Similar to this, C. cephalonica was also identified as a significant insect pest of many stored products in the tropics, affecting a variety of commodities, including oil seeds like groundnuts, cotton seeds, flax seeds, and oil-cakes (Bhandari et al 2014;Debbarma et al 2021;Vincent et al 2021). Typically, the destructive larval stage of C. cephalonica prefers to infest cracked or damaged grains, where it feeds beneath the formed silken threads, which over time gather density and bulk up the contaminated items (Chaudhuri and Senapati 2017).…”
Section: Discussionmentioning
confidence: 82%
“…Although there were no reports to date indicating either of the insect species identified in stored sesame seeds in Ethiopia, our current findings were consistent with earlier research that suggested that C. cephalonica was noted as a significant sesame storage pest in India (Babu et al 2020;Dilipsundar et al 2019). Similar to this, C. cephalonica was also identified as a significant insect pest of many stored products in the tropics, affecting a variety of commodities, including oil seeds like groundnuts, cotton seeds, flax seeds, and oil-cakes (Bhandari et al 2014;Debbarma et al 2021;Vincent et al 2021). Typically, the destructive larval stage of C. cephalonica prefers to infest cracked or damaged grains, where it feeds beneath the formed silken threads, which over time gather density and bulk up the contaminated items (Chaudhuri and Senapati 2017).…”
Section: Discussionmentioning
confidence: 82%